PELATIHAN TECHNOLOGICAL PEDAGOGIC CONTENT KNOWLEDGE (TPACK) PADA KOMUNITAS BELAJAR GURU DI KOTA PALANGKA RAYA - Bungai, Joni; Perdana, Indra; Kriswantara, Glory (LPPM Universitas Palangka Raya, 2024)
Innovative and creative teachers can be trained through socialization and training activities for teachers. This training and mentoring on Technological Pedagogical Content Knowledge (TPACK) aimed to enhance teachers' competence in designing learning tools that integrate technology, pedagogy, and content. The activities were conducted at SMAN 6 Palangka Raya, targeting a learning community of teachers. The training consisted of three stages: introduction, core activities, and conclusion. Evaluation results indicated that 90% of participants successfully understood and applied TPACK-based lesson planning. The program effectively improved teachers' understanding of technology integration in teaching. This community service aims to improve teacher understanding of technology integration in teaching, also to make innovative and creative teachers in classroom. Partnership Program This activity can provide direct benefits to improving the human resources of teachers in school.